Fostering Learner Autonomy through Contextual Teaching and Learning: Stake’s Countenance Evaluation at UII Dalwa - Achmad Naufal As Shiddiqy; Welly Kuswanto; Muhammad Khoirul Umam (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study evaluates how Contextual Teaching and Learning (CTL) fosters learner autonomy among Arabic Language Education students at Universitas Islam Internasional Darullughah Wadda'wah (UII Dalwa). A qualitative evaluative design was organised through Stake's Countenance Model, which examines antecedents, transactions, and outcomes while comparing intended instructional conditions with observed practice and evaluative standards. The empirical corpus comprised semi-structured lecturer interviews, classroom observations, and learning artefacts reported during the odd semester of the 2025/2026 academic year. The materials were organised in ATLAS.ti through document grouping, open coding, code consolidation, analytic memoing, and network mapping. The analysis identified a consequential movement across the three countenance components. Antecedent conditions were characterised by dependence on talaqqi, examination-oriented motivation, weak goal setting, and reliance on lecturer-provided resources despite an Arabic-rich pesantren environment. Transactional practices that disrupted these patterns included contextual problem orientation, guided inquiry, probing questions, rotating roles in learning communities, multiple forms of modelling, learning contracts, performance-based assessment, and weekly reflection. Outcomes were visible in more independent use of Maktabah Syamilah, Sinta-indexed journals, and digital dictionaries; improved self-evaluation; student-initiated Arabic discussion groups; and the production of Arabic educational content beyond the classroom. The evaluation nevertheless indicates that autonomy remained scaffold-dependent and uneven rather than complete. The study contributes an evidence-based account of how CTL can convert contextual exposure into purposeful learner agency when tasks, feedback, resources, and reflection are designed as an integrated cycle.